Right sided heart failure and pulmonary hypertension: New insights into disease mechanisms and treatment modalities. (December 2016) - Drogalis-Kim, Diana; Jefferies, John; Wilmot, Ivan; Alejos, Juan
Abstract: Pulmonary hypertension (PH), a rare chronic progressive disorder, is a well-established cause of right heart failure. Given that right heart function is the most important determinant of PH patient longevity Sandoval et al. (1994), D'Alonzo et al. (1991), Benza et al. (2010)[1–3], right heart pressure overload and failure secondary to PH is a critical aspect of the disease to review. In this article, we will highlight new research on the mechanisms of PH induced right heart failure, as well as review the latest PH treatments aimed at improving or sustaining right heart function.